Insulin-Like Growth Factors in the Pathogenesis and Treatment of Neurological Disorders in Children - Raili Riikonen (New Visions in Science and Technology Vol. 3, 2021)
Insulin-like growth factors (IGFs) play a key role for neuronal growth, differentiation, the survival of neurons and synaptic formation. The action of IGF-1 is most pronounced in the developing brain. In this paper we will try to give an answer to the following questions: Why are studies in children important? What clinical studies in neonatal asphyxia, infantile spasms, progressive encephalopathy–hypsarrhythmia–optical atrophy (PEHO) syndrome, infantile ceroid lipofuscinosis (INCL), autistic spectrum disorders (ASD) and subacute sclerosing panencephalitis (SSPE) have been carried out? Are there IGF-based therapeutic potentials? Do therapeutic approaches exist? Objective: The pathogenesis of some neurological disorders of children leading to intellectual disability, both acute and chronic diseases, was analyzed examining IGFs in serum and CSF combined with clinical data from the Finnish study and from the literature. In conclusion, there are now great hopes for the therapeutic use of IGF-1 for some neurological disorders, particularly ASD.